An approach to burr free precision metal stamping - Boey, Kok Hoong (2020)
The research study presented in this thesis is to evaluate the approach of burr-free in precision metal stamping. The primary process of the metal stamping always start from the metal separation process which may include the blanking operation and the piercing operation. These operations are to produce a cut-off blank of the intended geometry. The rationale of the inability to produce a burr-free blank lies on the understanding that burrs are the function of material’s ductility. The increasing popularity of the six sigma philosophy among original equipment manufacturers also has forced all metal components manufacturers to take in an interest in what most previously have considered unimportant – the burr edge. Now they must adjust their thinking to view burrs as a source of variation that can have adverse effects on product quality aside from added cost in the attempt to remove them. This formed a concrete motivation platform to continue and pursue on this research to derive a Burr-Free Technology (BFT) tool for a blanking operation gearing towards burr-free blank in one operation of the stamping process. Commercial package of LS-DYNA was used for the finite element modelling on blanking operation. The concluded numerical model was further validated with the experimental samples. The agreable numerical model was used to evaluate the potential inputs factors such as punch-die clearances, punch and die plate corner radius and the blanking load to the shear edge geometries such as die roll parameter, smooth shear zone parameter, the fracture initiation point and the fracture propagation patterns. The results obtained were used as a foundation for the BFT blanking tool design and fabrication. The fabricated BFT blanking tool was run under normal mass production mode to evaluate the effectiveness of the burr-free characteristic on the 1.0mm thick, JIS G3313 SECC work material. All experimental studies by BFT concept was performed under the conventional air clutch power press with the capacity of 110 ton. The presence of die rolls on edges at both planes of the blank signifies the onset of burr-free characteristic. The burr-free blanks finally was concluded with the BFT blanking tool structure on the case of lower punch protrude of 0.7mm with the correct pairing of positive clearances of 5% on upper punch and lower die and a negative clearance for lower punch and upper die. Aside, the optimum spring loads used for the upper die and lower punch forms an important parameter to the success of the burr-free blanking operation. The output of this BFT parameters produced the most desirable outputs in terms of the edge quality on burr-free blank. This was validated statistically through ANOVA method on the variance of the produced die rolls.